Democracy at the Village Level: Exploring the Leadership Style of Village Heads in Decision-Making - Nurwulan, Rahma; Permana, Ipik (Indonesian Journal of Advanced Research, 2025)
This study explores the inconsistency in leadership styles among village heads, focusing on the case of Keduanan Village, where leaders initially adopt a democratic approach but gradually shift toward authoritarian practices. Using Soerjono Soekanto's theory of leadership characteristics and a qualitative method through interviews, observations, and documentation, the study finds that although the Village Head claims to use a democratic leadership style, the practice lacks inclusivity and transparency. Key decisions are often made without involving relevant community groups or proper deliberation. The study concludes that there is a mismatch between the stated leadership style and its implementation, highlighting the need for improved democratic practices and more active community participation in village governance.